Tree‐Ring Inferred Seven Century Long Snowfall Record From the Cold‐Arid Western Himalaya, India - Krishna G. Misra; Vikram Singh; Ram R. Yadav; Sandhya Misra (International Journal of Climatology, 2025)
In the present study, Himalayan cedar samples from eight climate‐stressed sites were collected and used to examine the snowfall variability over the Lahaul‐Spiti region. The tree‐growth and climate relationship was explored using response function analysis, which revealed a positive tree‐growth relationship with precipitation and a negative relationship with temperature. The response function analysis also suggested that cool and moist climatic conditions favour tree growth, while warm and dry conditions reduce tree radial growth over the Lahaul‐Spiti region. Taking this relationship as a guide, we further tested the relationship of tree‐ring chronologies with observational Snow Water Equivalent (SWE) data. An observed statistically significant positive correlation encouraged us to develop the linear regression model for reconstruction. The linear regression models were used to develop a new November to April SWE record for the cold‐arid Lahaul‐Spiti region, Himachal Pradesh. The SWE reconstruction extends back to AD 1290 and revealed low SWE values in the year 1626 (223.6 mm), 1970 (254.4 mm), 1329 (270.1 mm), 1705 (271.9 mm), 2008 (278.5 mm), and high SWE values in the year 1306 (791.7 mm), 1348 (771.0 mm), 1412 (769.7 mm), 1569 (769.1 mm) and 1661 (765.9 mm). The reconstructed SWE is consistent with available precipitation, drought, and river flow records developed from different regions of the western Himalaya, underpinning its importance in understanding the regional hydro‐climatic variability. The cross‐field correlation analysis of the present SWE record with gridded precipitation, PDSI, and MADA also revealed a significant correlation for the westerly dominated Himalayan regions. The positive spatial correlation of SWE with snow cover area of the Northern Hemisphere further endorses the strength of our reconstruction. We also noted strong linkages of SWE with the El‐Niño Southern Oscillation in the present study, while the dominance of the Indo‐Pacific climate system is observed in the spectral analysis. Therefore, we believe that our attempt to develop a seven‐century‐long SWE record from a data‐scarce Himalayan region will strengthen our understanding of the hydrological variations in the long‐term perspective.

Climatic Oscillations and Dynastic Trends: A Multiproxy analysis of the past two millennia in the Indian Subcontinent - Anjali Trivedi; Shailesh Agrawal; Anupam Sharma; Sheikh Nawaz Ali; M.C. Manoj; Anupam Nag; Sandhya Misra; Masud Kawsar (CATENA, 2024)

Light and auxin responsive cytochrome P450s from Withania somnifera Dunal: cloning, expression and molecular modelling of two pairs of homologue genes with differential regulation - Sudhakar Srivastava; Rajender Singh Sangwan; Sandhya Tripathi; Bhawana Mishra; L. K. Narnoliya; L. N. Misra; Neelam S. Sangwan (Protoplasma, 2015)